Program Keluarga Berencana dalam Meningkatkan Kesejahteraan Keluarga : Family Planning Programme in Improving Family Welfare - Muhammad Zaldy Febry; Sitti Jamilah Amin; Muhiddin Bakri; Abd Rasyid (IAIN Parepare, 2024)
The Family Planning Programme strategy is a programme strategy with the main objective of fostering a quality family so as to provide opportunities for the community to plan family life towards a prosperous family. The purpose of this research is to find out what strategies are used in the Family Planning programme in improving family welfare in Lompoe Village. This research uses a descriptive qualitative method with a phenomenological approach. Data collection techniques are observation, interview and documentation, while data analysis techniques are data reduction, data presentation, data verification and conclusion drawing. The results showed that the condition of family welfare in Lompoe Village has not been fully achieved, especially in the aspect of psychological welfare. The psychological factor is the control of the soul in fostering a harmonious family is very important, because the family is the first place of education for children. Parents providing love, security and comfort in the family have an impact on forming a prosperous family. The family planning (KB) programme still suffers from many weaknesses in the area of supervision after the use of the programme, both hormonal and mechanical, the right solution in supervision has not yet been found. Bad stigma about family planning is also still an obstacle in the implementation of this programme, which ultimately leads to community rejection.